1966
DOI: 10.2478/cttr-2013-0136
|View full text |Cite
|
Sign up to set email alerts
|

Composition Studies on Tobacco. XXlll: Pyrolytic and Structural Investigations on the Polyphenol-amino Acid Pigments of Leaf

Abstract: The complex polyphenolic pigments of Turkish tobacco have been pyrolyzed to determine their possible contribution to the formation of aromatic compounds, especially polynuclear aromatic hydrocarbons (PAH), of smoke. The dark brown pigments were initially obtained by a basic aqueous extraction of tobacco. Various hydrolytic procedures showed the presence of rutin, chlorogenic acid, and a series of amino acids; some information on the structure of these pigments is presented. The pyrolysis of the pigments was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…In addition to proteins, brown pigments and the decomposition products of chlorophyll, which are generated in tobacco during leaf curing (21), may be part of the insoluble fraction. CHORTYK et al reported that the content of amino acids was calculated to be around 23 wt% in the brown pigments in Turkish tobacco (22). It is likely that the amino acid content in brown pigments contributes to the formation of PAAs as donator of amines, though the extent of the contribution is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to proteins, brown pigments and the decomposition products of chlorophyll, which are generated in tobacco during leaf curing (21), may be part of the insoluble fraction. CHORTYK et al reported that the content of amino acids was calculated to be around 23 wt% in the brown pigments in Turkish tobacco (22). It is likely that the amino acid content in brown pigments contributes to the formation of PAAs as donator of amines, though the extent of the contribution is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Table 1), and brown pigments can be removed and isolated from tobacco by extraction with water, methanol, acetone and aqueous methanol [22][23][24]40,[48][49][50]. Schlotzhauer et al [25] reported on the contributions of different solvent extracts to the overall yields of phenol and cresols by pyrolyzing the different extracts at 860 8C.…”
Section: Effect Of Water Extraction On Phenolic Compound Yieldsmentioning
confidence: 99%
“…It has been reported that chlorogenic acid (CGA) is a significant precursor to catechol [3,21,22,27,29,31]. During the curing of burley tobacco, CGA levels decrease due to interactions of CGA with polyphenol oxidase to form CGA-quinone and this in turn can form polymeric pigments by complexing with amino acids [38,40,41]. Burley tobacco is usually cured over a five to seven week period [39,42] whereas bright and oriental tobacco have similar curing times of between one to two weeks [21,38,39].…”
Section: Comparison Of Phenolic Yields From Bright Burley and Orienmentioning
confidence: 99%
“…Phenols and polyphenols have tumor-promoting activity (Wynder and Hoffman 1961). Hexoses, starch, and cellulose are the major sources of simple phenols (Wynder and Hoffman 1967), whereas the oxidation products of polyphenols prior to burning, namely brown pigments and lignin, are the suspected precursors of tumor promotors and initiators in cigarette smoke (Chortyk et al 1966;Wynder and Hoffmann 1967). Therefore, the possible means of minimizing these leaf constituents in tobacco leaves and smoke should be investigated.…”
mentioning
confidence: 99%
“…The development of low alkaloid (LA) Burley 21 (Legg et al 1970) (Andersen et al 1.970b) but decreased soluble polyphenols (Sheen and Calvert 1969 Brown pigment quantitation employed Chortyk's method (Chortyk et al 1966) (Reid and Lynch 1937 For personal use only. A stalk position X N rate interaction existed for cellulose content.…”
mentioning
confidence: 99%